2020
DOI: 10.3389/fcell.2020.00563
|View full text |Cite
|
Sign up to set email alerts
|

TILRR Promotes Migration of Immune Cells Through Induction of Soluble Inflammatory Mediators

Abstract: TILRR has been identified as an important modulator of inflammatory responses. It is associated with NF-κB activation, and inflammation. Our previous study showed that TILRR significantly increased the expression of many innate immune responsive genes and increased the production of several pro-inflammatory cytokines/chemokines by cervical epithelial cells. In this study, we evaluated the effect of TILRR-induced proinflammatory cytokines/chemokines on the migration of immune cells. The effect of culture supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…We examined the migration behavior of cells in Transwell assay and microfluidic device assay. Our data showed that monocytes (THP-1) and T-lymphocytes (MOLT-4) migrated significantly towards the TILRR-overexpressed cell culture supernatants and migrated longer distances [69]. Therefore, the data showed that TILRR-modulated production of soluble mediators can promote migration of immune cells, and have a potential role in inflammation-induced vaginal HIV-1 acquisition by attracting immune cells to the site of inflammation.…”
Section: Tilrr and Migration Of Hiv-1 Target Cellsmentioning
confidence: 62%
See 3 more Smart Citations
“…We examined the migration behavior of cells in Transwell assay and microfluidic device assay. Our data showed that monocytes (THP-1) and T-lymphocytes (MOLT-4) migrated significantly towards the TILRR-overexpressed cell culture supernatants and migrated longer distances [69]. Therefore, the data showed that TILRR-modulated production of soluble mediators can promote migration of immune cells, and have a potential role in inflammation-induced vaginal HIV-1 acquisition by attracting immune cells to the site of inflammation.…”
Section: Tilrr and Migration Of Hiv-1 Target Cellsmentioning
confidence: 62%
“…NF-κB transcription factor is one of the central regulators of many inflammatory genes [66] and inflammation [67,71]. NF-κB activation is potentiated by the association of TILRR with IL-1R1 receptor [4,65], and TILRR-associated NF-κB activation instigates the production of inflammatory cytokines/chemokines, and migration of immune cells [16,58,69]. Since cervical epithelial tissues express a high level of FREM1 mRNA [15], and TILRR is an isoform of FREM1 [60] and a major modulator of many inflammatory responsive genes in the NF-κB pathway [16], the expression of FREM1/TILRR in genital epithelial tissues may augment the inflammatory responses via NF-κB activation and the production of inflammatory mediators.…”
Section: Potential Role Of Frem1 and Its Isoform Tilrr In Vaginal Hiv-1 Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Our studies showed that TILRR is a major modulator of many inflammatory responsive genes in the NF-κB signal transduction pathway, increases chemokine and cytokine secretion by epithelial cells, and promotes migration of immune cells. 2 , 3 Inflammation promotes activation and localization of HIV target cells, and elevated cervicovaginal inflammation has been associated with a higher risk of HIV acquisition. 4 , 5 , 6 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%